2015
DOI: 10.1021/acs.jpcc.5b01389
|View full text |Cite
|
Sign up to set email alerts
|

Background-Free Bottom-Up Plasmonic Arrays with Increased Sensitivity, Specificity and Shelf Life for SERS Detection Schemes

Abstract: In utilizing the exceptional optical properties of metallic nanoparticles, surface enhanced Raman spectroscopy (SERS) is an excellent candidate for analytical detection schemes due to its molecular specificity and high sensitivity. To record reliable SERS signals, impurifications on the metallic surface contributing to the overall SERS signal, have to be removed. In this context, it is important to improve the nanostructures’ quality to implement SERS in routine analytical applications. Here, we report about a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…It is known that the SERS activity can deteriorate due to surface oxidation of the silver surface [ 88 ]. For increasing the long-term stability of SERS active silver films we have studied a thin layer of dielectric Al 2 O 3 as protective coating [ 89 ]. A 1 nm thick Al 2 O 3 film was deposited on top of the nanoporous silver film by ALD before adding the probe molecule RhB.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the SERS activity can deteriorate due to surface oxidation of the silver surface [ 88 ]. For increasing the long-term stability of SERS active silver films we have studied a thin layer of dielectric Al 2 O 3 as protective coating [ 89 ]. A 1 nm thick Al 2 O 3 film was deposited on top of the nanoporous silver film by ALD before adding the probe molecule RhB.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatically generated nanoparticles (EGNPs), formed out of flat plates of silver crystals, show a desert‐rose‐ or flower‐like structure and are noted as powerful bottom‐up SERS substrates . These structures have great capability in bioanalytics, e.g., the label‐free detection of plant pathogens or the detection of Sudan III in food matrixes, as shown recently.…”
Section: Resultsmentioning
confidence: 99%
“…with a 10 nm thick Al 2 O 3 protection layer using atomic layer deposition. 39 Preliminary simulations and measurements showed that this layer had negligible influence on the optical properties of the nanoboomerangs, i.e., on the hybridization of the LSPRs. For comparison, we also fabricated elements of a pMS structure using a lift-off process, resulting in nanostructures with a metal strip width of approximately 110 nm and various opening angles and arm lengths.…”
Section: Fabrication and Measurementmentioning
confidence: 97%